2007
DOI: 10.5194/angeo-25-2217-2007
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency wave sources in the outer magnetosphere, magnetosheath, and near Earth solar wind

Abstract: Abstract. The interaction of the solar wind with the Earth magnetosphere generates a broad variety of plasma waves through different mechanisms. The four Cluster spacecraft allow one to determine the regions where these waves are generated and their propagation directions. One of the tools which takes full advantage of the multi-point capabilities of the Cluster mission is the wave telescope technique which provides the wave vector using a plane wave representation. In order to determine the distance to the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…They found a higher level of plasma and magnetic field fluctuations in the foreshock than in the undisturbed solar wind and in the quasi-parallel magnetosheath than in the quasi-perpendicular magnetosheath. Constantinescu et al [2007] found a source of low-frequency waves in the electron foreshock and in the cusp region. Gutynska et al [2012] suggested that the solar wind is the source of coherent low-frequency fluctuations (10 −4 − 10 −3 Hz) in the magnetosheath, whereas higher-frequency fluctuations (up to 10 −1 Hz) are generated by local sources.…”
Section: Introductionmentioning
confidence: 99%
“…They found a higher level of plasma and magnetic field fluctuations in the foreshock than in the undisturbed solar wind and in the quasi-parallel magnetosheath than in the quasi-perpendicular magnetosheath. Constantinescu et al [2007] found a source of low-frequency waves in the electron foreshock and in the cusp region. Gutynska et al [2012] suggested that the solar wind is the source of coherent low-frequency fluctuations (10 −4 − 10 −3 Hz) in the magnetosheath, whereas higher-frequency fluctuations (up to 10 −1 Hz) are generated by local sources.…”
Section: Introductionmentioning
confidence: 99%
“…Pinçon and Lefeuvre (1991) expanded the method to include multidimensional (vectorial) observables and Motschmann et al (1996) further developed it in order to apply it to multipoint satellite measurements (e.g. Glassmeier et al, 2001;Narita et al, 2003;Constantinescu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This data pool will be further enriched by the measurements of the upcoming ESA/Swarm mission, a constellation of three satellites in three different polar orbits between 400 and 550 km altitude, which will be launched in 2013. This data pool provides unique opportunities to study ULF pulsations in the magnetosphere (e.g., Constantinescu et al, 2007;Usanova et al, 2008;Sarris et al, 2009;Picket et al, 2010). New analysis tools that can cope with increased volume of measurements by numerous spacecraft located at different regions of the magnetosphere, similar to the ones employed in the present study, will effectively enhance the scientific exploitation of the continuously accumulated data.…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed that toroidal and poloidal mode field line resonances together with compressional Pc5 waves account for most of the observed coherent pulsations observed in the outer magnetosphere (Anderson et al, 1990). Multipoint observations show that upstream ULF waves in the Pc3-4 bands are generated in the foreshock region and entering and propagating through the magnetosphere as compressional waves (Sakurai et al, 1999;Constantinescu et al, 2007;Heilig et al, 2007;Clausen et al, 2009).…”
Section: Introductionmentioning
confidence: 98%